(3cJGH GdSehes - (3jGQHhbG (B( (3HQjhbG (B) (3GdfHWj GdcSQGfjs
(3ChdgG (B:s
(3bGd CHh HcQ gPG cJGH LeYJ eG ajg ef GdcdGe Ydi GdSehe hYdGLGJgG ef cJGH hLOJg ef cJH QLd ef bOeGA GdcSOGfjjf s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3YQVJ dg McI TOjOI ai SWM HOfg hbdb hhLY ai GdMdb hGdeYOI TOjO Hf hgjH hEf SbjJ efg EeQBI MGed hRf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1425s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs